Corporate Innovation: Do Diverse Boards Help?. (5th February 2021) - An, Heng; Chen, Carl R.; Wu, Qun; Zhang, Ting
Abstract: We find that corporate innovation is positively related to board diversity as measured by a multidimensional index. The benefit of board diversity is more pronounced for firms with more complex operations, more experienced boards, and stronger external governance, suggesting that diverse boards have superior advising capacity. We find evidence to suggest that firms with diverse boards engage in more exploratory innovations and develop new technology in unfamiliar areas. As a result, they create a larger number of both most-cited and uncited patents. Finally, of the six different aspects of board diversity, professional diversity matters the most for corporate innovation.